O ensino-aprendizagem de espanhol na terceira idade - Doná, Débora Caroline [UNESP] (2015)
The extension project UNATI - Open University for Senior Citizens- aims together with the students of campus UNESP/Assis to offer the elderly community from the city of Assis courses that provide the inclusion of this audience in the social coexistence. In this way, the course of Spanish language, ministered by two students of Letters course, expands the cultural manifestations that this language cover and highlight the importance of learning a foreign language. After all, the knowledge of a language enriches and contributes to the construction of the personal knowledge and it favors the elderly to understand new values under a linguistic-cultural perspective. At the same time, are concretized acquaintanceship and stories.